2017
DOI: 10.17113/ftb.55.03.17.5133
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Fermentation Improved Textural behaviour, Phenolic Compounds and Antioxidant Activity of Chia (Salvia hispanica L.) Dough

Abstract: SummaryIn this work, autochthonous lactic acid bacteria (LAB) were isolated from chia (Salvia hispanica L.) dough and selected on the basis of the kinetics of acidifi cation and proteolytic activity. Strain no. C8, identifi ed as Lactobacillus plantarum C8, was selected and used as start er to obtain chia sourdough. Lactic acid fermentation increased the organic acid mass fractions (lactic, acetic and phenyl lactic acids to 12.3 g, 1.0 g and 23.8 μg per kg of dough respectively), and antioxidant activities, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…The results showed that the probiotic could grow and metabolize these pseudocereals and after 21 days of storage at 5 • C, the probiotic levels were higher than 6 Log CFU/mL, and thus over the limit required for probiotic food, except for the beverage with whole buckwheat flour. Another study reported that chia can be fermented by L. plantarum C8, and that after 24 h of fermentation, its overall characteristics were improved, such as the phenolic compound concentration and antioxidant activity [65]. Therefore, this pseudocereal could be a good matrix for the development of probiotic beverages.…”
Section: Fermented Pseudocereal Beveragesmentioning
confidence: 99%
“…The results showed that the probiotic could grow and metabolize these pseudocereals and after 21 days of storage at 5 • C, the probiotic levels were higher than 6 Log CFU/mL, and thus over the limit required for probiotic food, except for the beverage with whole buckwheat flour. Another study reported that chia can be fermented by L. plantarum C8, and that after 24 h of fermentation, its overall characteristics were improved, such as the phenolic compound concentration and antioxidant activity [65]. Therefore, this pseudocereal could be a good matrix for the development of probiotic beverages.…”
Section: Fermented Pseudocereal Beveragesmentioning
confidence: 99%
“…Chia seeds have been used in bakery products (Bustos et al, 2017;Costantini et al, 2014;Farrera-Rebollo et al, 2012;Huerta, Alves, Silva, da Kubota, & Rosa, 2016), but there is no information available about the use of a by-product of chia oil extraction. The aim of this study was to investigate the effects of the addition of chia waste on the quality of wheat and gluten-free breads and to compare the effects of adding the waste with the effects of adding whole seeds.…”
mentioning
confidence: 99%
“…Original chia sourdough starter culture is developed by a selection of autochthonous LAB strains with affiliation to the species L. plantarum. Chemical analysis of chia sourdough showed high antioxidant effectiveness, and total phenolic compounds increased with 25% after 24 h of fermentation by L. plantarum [51].…”
Section: Lab Pseudocereals Fermentation For the Development Of Foods mentioning
confidence: 97%
“…They are usually found in milk and dairy products but can be isolated from plant or animal sources-leaves, fruits, roots, faeces and compost [19]. They widely participate in cereal fermented products [6][7][8]17,18,22], as well as in spontaneously fermented amaranth, quinoa and chia sourdoughs [48][49][50][51][52].…”
Section: Lab Cereal Fermentation: Microbiology and Biochemistry Of Thmentioning
confidence: 99%